Teaching to teach Physical Education from a critical perspective. Effects of the transmission the craft in professional training - Bologna Liprandi, Carina (2022)
This article shares some of the results of the study carried out on the teaching task in profesional training in Physical Education. The Physical Education Teachers offered by the Faculty of Physical Education of the Provincial University of Córdoba were selected for the development of the research. The objective of the work was to describe and analyze how Physical Education is taught to teach, by investigating the ways of transmitting the profession in Teaching Practice and Residence classes III and IV, two curricular units that bring students closer to the teaching exercise and to the educational reality. in school Physical Education. From a qualitative and ethnographic approach, and from participatory observation and in-depth interviews, the empirical reference was built.